Long-term performance and metagenomic analysis of full-scale anaerobic granular sludge bioreactors for low aerobically-biodegradable synthetic fiber manufacturing wastewater treatment. (September 2020) - Wang, Wei-Kuang; Ni, Chen-Hua; Guo, Yue-Jie; Lin, Yu-Chung; Chun-Te Lin, Justin
Abstract: The synthetic fiber manufacturing wastewater (FMW) contained large amounts of tetrahydrofuran (THF), 3-buten-1-ol (BDO) and 1, 4-butanediol (BTO) and showed a high chemical oxygen demand (COD) of 7, 992 ± 2, 252 mg L −1 . Ratio of the biological oxygen demand (BOD5 ) and COD of the FMW stream was analyzed as only 0.094, which reflected the low aerobically biodegradable property. For complementing existed aerobic biological treatment process, an external circulation sludge bed (ECSB) system consisting of two full-scale anaerobic granular sludge (AnGS) bioreactors was constructed and continuous operation for more than 25 months. Even though feed fluctuations occurred, robust performance of the system was exhibited with consistent high removals of COD (85.5 ± 4.4%), THF (79.8 ± 8.6%), BDO and BTO (both 100%). Fractionation analyses of AnGS at nine heights of the two bioreactors showed that the bigger size (>0.5 mm) dominated at the bottom (>92.1%). Morphology and elemental analyses of AnGS were helpful to see surface depositions in line with water analyses. Anaerobic biodegradations were also highlighted in a comprehensive analysis of carbon and nitrogen fractions, phosphates, sulfates and other minerals. Moreover, metagenomic analyses revealed Methanomicrobia and Methanosaeta in archaea and Exilispira in bacteria were the dominant genera in microbial community structure, which given more insights of anaerobic biodegradation in the two full-scale bioreactors. Highlights: Ratio of (BOD5 /COD) of fiber manufacturing wastewater (FMW) was determined as only 0.094. Full-scale AnGS bioreactors for synthetic FMW treatment were firstly long-term studied. Size fractionations of granular sludge showed larger (>0.5 mm) dominated at the bottom (>92.1%). Methanomicrobia, Methanosaeta, and Exilispira are major genera in metagenomic analyses. High anaerobic biodegradation of THF, BDO and BTO in FMW were achieved in the ECSB system.